Effects of Nitrogen and Potassium Fertilization on Yield and Nutritional Quality of Rangeland - TURK , MEVLUT; BAYRAM, GAMZE; BUDAKLI, EMINE; Celik, Necmettin (Asian Journal of Chemistry, 2010)
This research was conducted to investigate effects of nitrogen and potassium on yield and quality of rangelands in Turkey between 2001 and 2003. The research was set up as randomized complete block design with three replications. Four different nitrogen doses (0, 50, 100 and 150 kg ha-1) and three different potassium doses (0, 50 and 100 kg ha-1) were applied and their effects on rangeland was investigated. Ammonium nitrate and potassium sulphate was used as nitrogenous and potassium fertilizers. All of potassium fertilizer and 50% of nitrogenous fertilizer were be applied in Fall and the remaining amount was used in Spring. Effects of fertilizer applications on dry matter yield, crude protein concentration, crude cellulose ratio, crude ash ratio, magnesium, calcium, potassium concentrations and tetany ratios were investigated. Averaged over two years, nitrogen doses increased dry matter yield, crude protein concentration, crude cellulose ratio, crude ash ratio, potassium concentration and tetany ratio, while nitrogen doses decreased magnesium concentration. Potassium doses increased crude protein concentration, potassium concentration and tetany ratio, while it decreased magnesium and calcium concentration. According to results of this study, the highest dry matter yield was obtained from in N150K0 (9.93 g kg-1) and N150K50 (10.01 g kg-1) treatments. N150K100 application has the highest crude protein concentration (141.3 g kg-1). The highest crude cellulose ratio (49.90 %) was obtained from in N150K50. Tetany ratios (K/Ca+Mg) exceeded the critical level in N50K100, N100K100 and N150K100 treatments.